(untitled) (Politeja, 2023)
The article aims to show contemporary artistic interpretations of colonialism in Portugal as expressed by Afro-descendants from former Portuguese colonies. The primary focus of this study is the ongoing debate surrounding two monuments in Lisbon. The first monument, the Padrão dos Descobrimentos, was originally created in 1940 and subsequently rebuilt in 1960 and is still one of the city’s most recognizable landmarks. The second monument, the Memorial to Enslaved People, is currently under development and seeks to give voice to African communities in Portugal. The analysis is grounded in a theoretical framework that incorporates concepts such as postmemory, multidirectional memory, and dissonant heritage. The broader context for this study is the UNESCO Decade of People of African Descent (2015-2024).